Care management for people with venous ulcers from the perspective of health quality (Research, Society and Development, 2020)
This study aims to reflect on the management of care for people with venous ulcers from the perspective of quality in health. It is a theoretical-reflective study, anchored in the perspective of health quality proposed by Avedis Donabedian and in the ABC Model present in the document entitled “Simplifying venous leg ulcer management. Consensus recommendations” that values optimizing the management of venous ulcers. The reflections presented in this study point out that care management must go beyond what is proposed in the ABC model, and must, through management technology, address the biopsychosocial and spiritual spheres, in order to make care holistic, as well as promote innovations that underpin the quality in health. Given the above, it is understood that the management of care associated with the quality of health of people with venous ulcers uses management technology without considering care in all its complexity and specificity, being urgent to think about providing the best possible well-being directly associated with quality of life.